2015
DOI: 10.1186/s40697-015-0073-6
|View full text |Cite
|
Sign up to set email alerts
|

Time to Revisit the Problem of CIN? The Low Incidence of Acute Kidney Injury with and without Contrast in Hospitalized Patients: An Observational Cohort Study

Abstract: BackgroundAcute kidney injury (AKI) following imaging procedures with contrast medium in hospitalized patients is commonly attributed to contrast-induced nephropathy (CIN). This study sought to establish a benchmark of the incidence of AKI in hospitalized patients who underwent computed tomography (CT) scans, with and without intravenous contrast administration.MethodsThis was a multi-center observational cohort study. Hospitalized patients in four hospitals with CT scans during two time periods in 2012 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
3
Order By: Relevance
“…In a controlled prospective observational study, Hemmett et al 4 reported an incidence of AKI of about 11% in 843 inpatients. However, the incidence of AKI was similar in the group given contrast and in the group not given intravenous iodinated contrast.…”
Section: Contrast Induced Nephropathymentioning
confidence: 99%
“…In a controlled prospective observational study, Hemmett et al 4 reported an incidence of AKI of about 11% in 843 inpatients. However, the incidence of AKI was similar in the group given contrast and in the group not given intravenous iodinated contrast.…”
Section: Contrast Induced Nephropathymentioning
confidence: 99%
“…CIN, often underdiagnosed, is considered the third cause of ARF in a hospital setting, and may correspond to 12% of cases, remaining behind only prerenal and druginduced ARF [2][3] . In this study, a higher prevalence was observed, corresponding to 30.38% (n = 24) of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…During last decade, CIN has been identified as the third leading cause of acute renal failure (ARF) in hospitalized patients and may reach 12% of cases. This complication increases mortality, morbidity, length of hospitalization and associated costs [2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…A split-bolus technique combines different contrast phases into one acquisition, thereby diminishing radiation exposure with only limited increase in the amount of contrast medium. Many studies showed that intravenous administration of contrast media was not as harmful as using the intra-arterial route [ 20 22 ]. Although the dose of the contrast medium was increased in the split-bolus MDCT protocol compared with the multiphase MDCT protocol, the radiation dose also clearly reduced.…”
Section: Discussionmentioning
confidence: 99%